Comparative High-Resolution X-Ray Diffraction Analysis of GaN/AlGaN Heterostructure on Al2O3 and Si (111) Substrate Grown by Plasma Assisted Molecular Beam Epitaxy. Issue 1754 (7th May 2015) - Jana, Sanjay Kr.; Ghosh, Saptarsi; Dinara, Syed Mukulika; Chakraorty, Apurba; Biswas, D.
Abstract: The work presents a comparative study on GaN/AlGaN type-II heterostructures grown on c-plane Al2 O3 and Si (111) substrates by Plasma Assisted Molecular Beam Epitaxy. The in-depth structural characterizations of these samples were performed by High-Resolution X-Ray Diffraction, X-ray Reflectivity and Field Emission Scanning Electron Microscopy. The in-plane and out-of plane strains were determined from measured c- and a-lattice parameters of the epilayers from reciprocal space mapping of both symmetric triple axis (002) and asymmetric grazing incidence (105) double axis mode. The mosaicity parameters like tilt and correlation lengths were also calculated from reciprocal space mapping. Moreover, the twist angle was measured from skew symmetric off axis scan of (102), (103), and (105) planes along with (002) symmetric plane. The defect density were measured from the full width at half maxima of skew symmetric scan of (002) and (102) reflection planes. Also, the strained states of all the layers were analyzed and corresponding Al mole fraction was calculated based on anisotropic elastic theory. The thicknesses of the layers were measured from simulation of the nominal structure by fitting with X-ray Reflectivity experimental curves and also by comparing with cross sectional Field Emission Scanning Electron Microscopy micrographs.